Analisis Pola Pembelian Produk Menggunakan Algoritma Apriori - Sigalingging, Iska Heriyati; Harman, Rika (Forum Kerjasama Pendidikan Tinggi, 2020)
The development of technology in Indonesia is developing so rapidly. This development can be seen from various retails that have used a computerized system in carrying out the buying and selling process. One minimarket that has used a computerized system in the buying and selling process is the Al Barokah Mart Shop. In taking data by interview and observation, this research uses quantitative methods. The purpose of this research is to find out the pattern of arrangement of goods in the minimarket and analyze how the patterns of purchase from consumers. In managing the data obtained, the associatin rules method is used to look for patterns of relationships between items that often appear in many transactions. The process of determining product purchasing patterns is done by applying data mining with a priori algorithm method, then the results obtained in the highest Al Barokah Mart case that appear on egg and indomie items with a support value of 46.66% and a confidence value of 87.50, while indomie and eggs with a support value of 46.66% and a confidence value of 63.63%.